Integrated plasmonic circuitry on a vertical-cavity surface-emitting semiconductor laser platform - Cillian P. T. McPolin (Nature Portfolio, 2016)
Integrated plasmonic sources are crucial in the development of plasmonic circuitry. Here, McPolin et al. show that vertical-cavity surface-emitting lasers can be employed as an on-chip, electrically pumped source or detector of plasmonic signals and also demonstrate waveguiding and frequency conversion on this platform.